#### Answer

(-2, 3)

#### Work Step by Step

Multiply the first equation by 2
4x + 2y = -2
Add to the second equation
4x + 2y = -2
x - 2y = -8
5x = -10
x = -2
Plug x = -2 into x - 2y = -8
-2 - 2y = -8
-2y = -6
y = 3
Solution is (-2, 3)

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

(-2, 3)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.